A socio-economic picture of Kosovar migrants and their origin farm households; Sozioökonomische Einsichten in kosovarische Migrantenhaushalte in Deutschland und in ihre ländlichen Ursprungshaushalte im Kosovo - Judith Möllers; Wiebke Meyer; Sherif Xhema; Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
Kosovo's small economy substantially relies on money from abroad: an extraordinarily high number of migrants contribute to foreign capital inflow through remittances; remittances represented around 13% of gross domestic product (GDP) in 2009. This means that the well-being of many Kosovar families financially depends on their migrated family members (UNDP 2010). The most important destination of Kosovar migrants, Germany, alone hosts an estimated number of around 300,000 Albanian migrants from Kosovo. This is about half of all migrated Kosovar Albanians. However, reliable information on the specific situation of the migrants and their origin households is scarce. Adding to recent efforts to gain more knowledge about Kosovo and its remittances sending migrants, e.g. the UNDP's 2010 Kosovo Remittance Study, this discussion paper puts a specific focus on rural Kosovo, where many migrants come from and more than half of the Kosovar population and two thirds of the poor live (World Bank and SOK 2011). Our study aims at shedding light on the socio-economic situation of Kosovar farm households with migrants in Germany. We present data on both sides of migration: the migrant household in the destination country as well as the remittances receiving household in Kosovo. In our analysis of migrant households, we present results on socio-economic features of three migration waves. Individual demographic characteristics of the migrant are analysed as well as economic features including the income situation and the remitting behaviour. We furthermore discuss the nature of migration - if it is planned as a temporary or permanent move - and the return prospects of the migrants. For the corresponding farm households in Kosovo we present results on their socio-economic situation and specifically look at poverty and inequality indicators and discuss possible development impacts in the recipient households. We analyse an original sample of 226 Albanian migrants from Kosovo who have been interviewed by means of a structured questionnaire in 2009/10 in Germany as well as the corresponding sample of their origin farm households in rural Kosovo. For a comparison of recipient with non-recipient households we draw from an additional set of 55 non-recipient Kosovar households. – – Die kosovarische Wirtschaft hängt stark von Geldflüssen aus dem Ausland ab. Eine hohe Zahl von Migranten tragen mit sogenannten Rücksendungen zu diesem Auslandskapital bei. Die Rücksendungen machen etwa 11% des Bruttoinlandsprodukts des Kosovo im Jahr 2009 aus. Das bedeutet, dass viele kosovarische Familien finanziell von ihren migrierten Familienmitgliedern abhängen. Das Hauptzielland von Migranten aus dem Kosovo ist Deutschland, wo allein geschätzte 300 000 albanische Migranten aus dem Kosovo zu verzeichnen sind, und somit in etwa die Hälftealler albanischen Migranten aus dem Kosovo. Genaue und belastbare Angaben über die Situation dieser Migranten und über die Situation ihrer Heimathaushalte sind bis heute nur schwer zu erlangen. Dieses Diskussionspapier stellt einige neue, empirisch basierte Erkenntnisse vor, indem es mit einem Fokus auf den ländlichen Raum des Kosovo einige wichtige Facetten ergänzt, die auch in anderen aktuellen Studien, beispielsweise die 2010 Kosovo Remittance Study der UNDP, angesprochen werden. Der ländliche Raum ist deshalb so wichtig, weil viele Migranten von hier stammen und etwa die Hälfte der Bevölkerung des Kosovo und zwei Drittel der armen Bevölkerung hier leben. Unsere Ergebnisse befassen sich mit der speziellen Situation kleinbäuerlicher Haushalte im Kosovo sowie der zu diesen Haushalten gehörigen Arbeitsmigranten in Deutschland. Es werden hierbei beide Seiten der Migration ins Auge gefasst, also sowohl die Migranten selbst als auch die Ursprungshaushalte aus dem ländlichen Kosovo, die von Rücksendungen profitieren. Im Bezug auf die Migranten präsentieren wir Ergebnisse im Hinblick auf drei Migrationswellen. Wir betrachten individuelle und haushaltsbasierte Migrationsmotive und geben Einblick in die soziökonomische Situation der Migranten. Wir gehen dabei auch auf die Dauer der Migration und die Rückkehrwahrscheinlichkeit ein. Die Ursprungshaushalte werden ebenfallsim Hinblick auf sozioökonomische Variablen hin analysiert. Wir diskutieren hier speziell die Wirkungen der Geldsendungen auf Armut, Ungleichheit und mögliche Entwicklungseffekte. Die Datenbasis unserer Analyse ergibt sich aus einem Sample von 226 albanischen Migrantenhaushalten aus dem Kosovo, die im Winter 2009/10 in Deutschland interviewt wurden. Ebenfalls Teil der Erhebung sind die dazugehörigen Ursprungshaushalte, die im Anschluss im Kosovo interviewt wurden. Für einen Vergleich von Geldsendungsempfängern und Haushalten die keine Geldsendungen erhalten, stützen wir uns auf einen ergänzenden Datensatz von 55 Nicht-Geldsendungsempfängern.
urn:nbn:de:gbv:3:2-27305
Keywords: F22; F24; O15; 330; migration; remittances; Kosovo; rural households; Migration; Rücksendungen; Kosovo; Ländliche Haushalte